The Libycosaurus (Hippopotamoidea, Artiodactyla) intercontinental dispersal event at the early late Miocene revealed by new fossil remains from Kasserine area, Tunisia. (1st February 2021) - Lihoreau, Fabrice; Essid, El Mabrouk; Khayati Ammar, Hayet; Marivaux, Laurent; Marzougui, Wissem; Tabuce, Rodolphe; Temani, Rim; Vianey-Liaud, Monique; Merzeraud, Gilles
ABSTRACT: Anthracotheres dispersed from Asia toward Africa at least three times: at the Eocene/Oligocene transition, during the early Miocene and later during the Miocene. Those dispersals are important datum events for African Tertiary biochronology. New fossil remains of early Libycosaurus, the genus implicated in the late Miocene dispersal, are described from a new Tunisian locality of the Kasserine area. The new fossils enhance the hypodigm of Libycosaurus algeriensis and increase the resolution of the phylogenetic position of this species using cladistics analysis. The inclusion of the genus Libycosaurus within the well-described Merycopotamus lineage allows us to constrain its dispersal time. Dispersal of this anthracothere from the Indian sub-continent to Africa was probably facilitated by sea level decrease during the early Tortonian, just preceding the Hipparion dispersal event. This new age estimation refines the resolution of the succession of late Miocene deposits in Maghreb and frames the date of the onset of the Sahara.